2022
DOI: 10.3390/medicina58091202
|View full text |Cite
|
Sign up to set email alerts
|

Absolute and Functional Iron Deficiency in Colon Cancer: A Cohort Study

Abstract: Background and Objectives: Iron is an essential micronutrient for many biological functions and has been found to be intimately linked to cancer biology. Although the effects of increased dietary iron consumption in the development of CRC have been previously investigated in several cohort studies, the available evidence on the involvement of iron deficiency in this process is relatively scarce. Previously published papers did not analyze specific outcomes, such as the presence of biologically aggressive histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…FID without anemia is also common in critical illness. FID, measured by red cell hypochromasia on flow cytometry and presence of zinc protoporphyrin, represents an insufficient biological availability of iron in the presence of adequate storage reserves [14,15]. In a prospective observational study, it was reported that the incidence of FID reached up to 35% in patients at admission [4].…”
Section: Iron Metabolism In Critically Ill Patientsmentioning
confidence: 99%
“…FID without anemia is also common in critical illness. FID, measured by red cell hypochromasia on flow cytometry and presence of zinc protoporphyrin, represents an insufficient biological availability of iron in the presence of adequate storage reserves [14,15]. In a prospective observational study, it was reported that the incidence of FID reached up to 35% in patients at admission [4].…”
Section: Iron Metabolism In Critically Ill Patientsmentioning
confidence: 99%
“…An absolute iron deficiency in colorectal cancer can impair not only the cardiac and respiratory functions, among others, but also the immune system’s defence. Deficient patients could be affected more and could present with more advanced disease–lymphatic invasion, as shown by Fagarasan et al [ 12 ].…”
mentioning
confidence: 99%